Research on the impact of green finance on the upgrading of China's regional industrial structure from the perspective of sustainable development - Wang, Xinyue; Wang, Qing (Resources policy, 2021)
Green finance is a mechanism with which to provide financial support for green projects, promote technological progress, and facilitate the green and sustainable development of the economy. Therefore, it is an important driving force of green economic growth and structural transformation. The development of green finance is a strategic move to promote the upgrading of industrial structure, achieve green development, and accelerate ecological civilization. In this study, based on data from the period of 2008–2020, the gray correlation method was used to empirically test the relationship between green finance and the upgrading of industrial structure in China. For this purpose, the system GMM model was used to determine the direction and the impact degree of green finance on the upgrading of industrial structure. The results show that the correlation between green finance and output value is highest in the tertiary industry, followed by the primary and secondary industries. Thus, China's green finance has the strongest effect on the tertiary industry and will lead to its rapid development, promoting the upgrading of industrial structure. The regression coefficients of human capital, R&D innovation capability, degree of openness, government expenditure level, and urbanization level are all positive, indicating that enhancing these elements can significantly promote the upgrading of industrial structure. The effects of green finance on the upgrading of industrial structure differ among the east, central, and west regions; these significant regional differences reflect an unbalanced state. The regression coefficient of the eastern region is relatively large and is significantly higher than that of the central and western regions, but they all indicate significant positive effects. Finally, based on the results of empirical analysis, this paper explores green finance policy measures, such as improving the development of green technology innovation, strengthening foreign exchange and cooperation in green finance, training green finance professionals, and implementing green finance infrastructure. ·From the Perspective of Sustainable Development.·Use gray correlation method to empirically test the relationship.·Use system GMM model to verify the impact.·Provide reference for Sustainable Development.